Genomic Markers Associated With Soybean Resistance to the Stem Borer, Dectes texanus (Coleoptera: Cerambycidae) - Sarah Johnson; David Hyten (Plant Direct, 2025)
ABSTRACT The Dectes stem borer, Dectes texanus LeConte (Coleoptera: Cerambycidae), can significantly reduce yields by causing significant lodging in soybean. While this stem borer has not been considered a major pest of soybean, damage from it is increasing in the United States Midwest region with no current elite cultivars found resistant. Our objective was to map quantitative trait loci (QTL) that reduce girdled stems caused by Dectes stem borer infection and infestation of Dectes stem borer. A genome‐wide association study (GWAS) using 50,000 single nucleotide polymorphisms was used to analyze data from a population of maturity group (MG) V to VII soybean accessions grown in North Carolina, which had been scored for Dectes stem borer larvae infestation and girdled stems caused by Dectes stem borer infestation. The GWAS identified 3 QTL with reduced larvae infestation and 4 QTL for reduced girdled stems. Allele effects ranged from 1% to 9% reduced larvae infestation or girdled stems. The QTL identified and germplasm containing the beneficial alleles can be used for improving resistance to the damage caused by the Dectes stem borer in elite soybean cultivars.